2017
DOI: 10.7759/cureus.2008
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Consuming Junk Food among Saudi Adults in Jeddah City

Abstract: IntroductionJunk food (JF) consumption trend is increasing in all parts of the world. The transition in lifestyle and dietary habits is leading to many non-communicable diseases. The objectives of this study are twofold: (1) To examine the prevalence of junk food consumption and factors associated with consuming junk food among Saudi adults in Jeddah; and (2) to compare the trends of junk food consumption among males and females in Jeddah.MethodologyThis cross-sectional study was conducted in five different Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 20 publications
3
20
0
Order By: Relevance
“…The transition in lifestyle and dietary habits may be responsible for this trend and it is directly or indirectly leading to rise of many non-communicable diseases. 1 Most parents are hardly aware of the fact that local foods produced by them are far cheaper and more nutritious. 2 Despite this fact, consumption trend of junk foods is increasing all over the world.…”
Section: Introductionmentioning
confidence: 99%
“…The transition in lifestyle and dietary habits may be responsible for this trend and it is directly or indirectly leading to rise of many non-communicable diseases. 1 Most parents are hardly aware of the fact that local foods produced by them are far cheaper and more nutritious. 2 Despite this fact, consumption trend of junk foods is increasing all over the world.…”
Section: Introductionmentioning
confidence: 99%
“…2 A study conducted by Bhutani et al found that eating once per week from a fastfood restaurant increases the body mass index (BMI) yearly by 0.8 kg/m2, whereas eating in dine-in restaurants increases it by 0.6 kg/m 2.3 These numbers are especially alarming for Saudi Arabia, since a study conducted by Mandoura et al in Jeddah showed that the majority of Saudi adults (86.5%) reported regular consumption of junk food, where 35.6% and 36.2% of the males and females, respectively, consume junk food from two to five times per week. 4 In 2016, Saudi Arabia launched the Kingdom's 2030 vision as a road map for economic growth and national development of the country. The vision consists of eight themes, and 96 strategic objectives which will be achieved by 2030 through both governmental, and non-governmental bodies in the country.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to investigate dietary quality among adults in the KSA (Al-Shoshan, 2007; Moradi-Lakeh et al, 2017; Thorpe et al, 2014). Most of these studies have assessed diet quality based on either a diet history questionnaire that did not contain details of all types of foods and beverages (Al-Shoshan, 2007; Mandoura et al, 2017; Moradi-Lakeh et al, 2017) or Saudi dietary guidelines (Alkhaldy et al, 2019; Saudi Ministry of Health, 2012). Moreover, one study used the dietary guideline index (DGI), which was designed to assess adherence to Australian dietary guidelines (Thorpe et al, 2014).…”
Section: Introductionmentioning
confidence: 99%